2003
DOI: 10.1021/jf0209589
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a t,t Conjugated Linoleic Acid Methylester (CLA-Me) Isomers Mixture from Synthetic CLA by Methylation with BF3/Methanol

Abstract: Mixtures of t,t conjugated linoleic acid methylester (t,t CLA-Me) isomers were prepared from synthetic CLA, consisting of 47.8% t10,c12 CLA; 45.5% c9,t11 CLA; 2.0% t,t CLA; and 4.7% others, by methylation with BF(3)/methanol (designated TT-TC/CT) in conjunction with purification at -68 degrees C for 24 h. The amount or composition of the TT-TC/CT was greatly affected by the concentration of BF(3) in methanol and the duration of methylation. The methylation of 50 mg of synthetic CLA for 30 min with 1 mL of 7.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The c 9, t 11 and t 10, c 12 CLA were prepared from synthetic CLA methyl ester (Kim and others 2000), and the t,t CLA was prepared from synthetic CLA (Kim and others 2003). The purity of CLA isomers was 99% t 10, c 12 CLA, 90.3% c 9, t 11 CLA, and 96% t,t CLA when analyzed by GC described subsequently.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The c 9, t 11 and t 10, c 12 CLA were prepared from synthetic CLA methyl ester (Kim and others 2000), and the t,t CLA was prepared from synthetic CLA (Kim and others 2003). The purity of CLA isomers was 99% t 10, c 12 CLA, 90.3% c 9, t 11 CLA, and 96% t,t CLA when analyzed by GC described subsequently.…”
Section: Methodsmentioning
confidence: 99%
“…The Ag + ‐HPLC analysis of the t,t CLA‐Me was carried out using a Young‐Lin M930 solvent delivery system (Anyang, Korea) with a UV detector (M720) operated at 233 nm and an operating system (Autochro‐win version 2.0) (Kim and others 2003). Two ChromSpher 5 Lipids analytical silver‐impregnated columns (4.6 mm i.d.…”
Section: Preparations and Analysis Of Membrane Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ju and Jung [15] showed that soy oil hydrogenation could be manipulated to produce 12 % trans,trans-CLA by adding sulfur with nickel as a catalyst; however, this process was accompanied with the formation of 19 % elaidic acid which is undesirable in food-grade oil [15]. trans,trans-CLA FAME were produced from synthetic CLA free fatty acids using BF 3methanol catalyzed methylation [16]; however, this method was unable to directly produce trans,trans-CLA TAG and the process is laborious and time consuming taking over 24 h to complete.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in fried ground beef, CLA has gained attention because of its important biofunctional activities, especially for its anti-carcinogenic and body fat reduction properties. In synthetic CLA, c 9, t 11-CLA and t 10, c 12-CLA isomers predominate and t 9, t 11-CLA and t 10, t 12-CLA are present as minor components . The anti-carcinogenic effects of different CLA isomers have been evaluated in many human cancer cell lines and animal models.…”
Section: Introductionmentioning
confidence: 99%